Research Progress in the Extraction and Rapid Determination of Inorganic Arsenic in Food - Wei TIAN; Minghui ZHOU; Jieqiong ZHANG; Yonglin LIU; Xi CHEN; Yanxiang WU; Songxue WANG (Shipin gongye ke-ji, 2022)
Arsenic is a common toxic element, and has been widely found in nature environment. Arsenic and its compounds are also widely used in pesticides, coating materials, medicine and other fields. Food safety problems caused by arsenic are frequently taken place in the world. Among them, inorganic arsenic is the most toxic and has been recognized as the I class of carcinogens by the International Agency for Research on Cancer. In terms of food safety supervision, the rapid and accurate determination of inorganic arsenic in food will be the primary measure to control its harm to human health, and it also will be the basis technique for related researches. In recent years, the combination of Atomic fluorescence spectroscopy with chromatography and the combination of inductively coupled plasma mass spectrometry (ICP-MS) with chromatography have been the main methods for the detection of inorganic arsenic. However, the conventional detection methods have some problems such as complicated pretreatment procedure and long detection time. Therefore, it is of great significance to develop rapid pretreatment and rapid detection technology for improving the ability of rapid screening and risk assessment of inorganic arsenic in food. At present, many of new research methods on the rapid extraction and detection of arsenic in food are studied by domestic and foreign scholars. In this paper, some extraction and rapid detection methods of inorganic arsenic in food are reviewed to provide reference for related research.